Bacterial pneumonia induces senescence in resident alveolar macrophages that are outcompeted by monocytes - Jinjing Zhang; Tao Wang; Yanling Wang; Ying Li; Lu Wang; Jiepu Wang; Yuxuan Miao; Feng Xu; Yushi Yao (Cell Reports)
Summary: Alveolar macrophages (AMs) are lung-resident macrophages critical to lung homeostasis and immunity. Replacement of embryonic-derived tissue-resident AMs (TRAMs) by circulating monocyte-derived AMs (MoAMs) reshapes the functionality of AMs and host susceptibility to respiratory diseases. However, mechanisms underlying such an AM turnover remain unclear. Using a mouse model of Streptococcus pneumoniae (S.P.) infection, we show here that respiratory S.P. infection induces the recruitment and differentiation of MoAMs, which dominate the post-infectious AM population and are functionally hyperresponsive. This turnover of AMs is not due to S.P.-induced irreversible loss of TRAMs. Instead, TRAMs experience a quick recovery in cell number shortly after the resolution of S.P. infection. While S.P.-experienced TRAMs keep the potential of long-term self-maintenance in a non-competitive environment, they demonstrate cellular senescence and a reduced rate of homeostatic proliferation and are, therefore, outcompeted by MoAMs. These data provide new insights into the mechanisms and functional significance of AM turnover during pulmonary bacterial infection.